2022
DOI: 10.1021/acs.jproteome.2c00203
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup-Enriched Pathways and Kinase Signatures in Medulloblastoma Patient-Derived Xenografts

Abstract: Medulloblastoma (MB) is the most common malignant pediatric brain tumor. MB is classified into four primary molecular subgroups: wingless (WNT), sonic hedgehog (SHH), Group 3 (G3), and Group 4 (G4), and further genomic and proteomic subtypes have been reported. Subgroup heterogeneity and few actionable mutations have hindered the development of targeted therapies, especially for G3 MB, which has a particularly poor prognosis. To identify novel therapeutic targets for MB, we performed mass spectrometry-based de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Activation of Shh signaling increased phosphorylation of p38, and inhibition of p38 significantly attenuated Shh-dependent upregulation of Gli1 in astrocytes 39 , whereas phospho-p38 levels in the joint tissue of collagen-induced arthritis was decreased after blockade of SHH signaling 40 . However, a previous study on children MB SHH -derived xenografts indicated p38 kinase MAP2K3/MKK3 and the p38 effector MAPKAPK2/MK2 were significantly upregulated, as compared to Group 3 or 4 MB xenografts 41 , and a previous study demonstrated the level of p38α increased significantly during the proliferation of cerebellar granule cell precursors, and inhibition of SHH signaling or granule cell precursor proliferation decreased p38α levels 42 . These findings appear to be at odds with our study that p38 is inactivated in children and mouse MB SHH .…”
Section: Discussionmentioning
confidence: 91%
“…Activation of Shh signaling increased phosphorylation of p38, and inhibition of p38 significantly attenuated Shh-dependent upregulation of Gli1 in astrocytes 39 , whereas phospho-p38 levels in the joint tissue of collagen-induced arthritis was decreased after blockade of SHH signaling 40 . However, a previous study on children MB SHH -derived xenografts indicated p38 kinase MAP2K3/MKK3 and the p38 effector MAPKAPK2/MK2 were significantly upregulated, as compared to Group 3 or 4 MB xenografts 41 , and a previous study demonstrated the level of p38α increased significantly during the proliferation of cerebellar granule cell precursors, and inhibition of SHH signaling or granule cell precursor proliferation decreased p38α levels 42 . These findings appear to be at odds with our study that p38 is inactivated in children and mouse MB SHH .…”
Section: Discussionmentioning
confidence: 91%